GOOD CORPORATE GOVERNANCE MEMODERASI HUBUNGAN KOMPENSASI EKSEKUTIF, PREFERENSI RISIKO EKSEKUTIF DAN KONEKSI POLITIK DENGAN TAX AVOIDANCE - Ade Firmansyah; Suripto; Iin Rosini (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
The phenomenon of tax avoidance practices in Indonesia, as revealed by the Directorate General of Taxes and the Tax Justice Network and carried out by several large companies, is closely related to corporate governance activities, resulting in a state loss of 2,736 million US Dollars within one year. This research aims to examine and analyze how Good Corporate Governance moderates the relationship between executive compensation, executive risk preferences, and political connections with tax avoidance. This study uses an associative quantitative research design. The population for this research includes all companies listed in the IDX80 on the Indonesia Stock Exchange from 2020 to 2024, totaling 80 companies. The sample was determined using saturation sampling, yielding 80 companies over a five-year period, resulting in 400 data observations. Data analysis was performed using panel data regression with E-views version 12 as the analytical tool. The results show that executive compensation has a positive effect on tax avoidance, while executive risk preferences and political connections do not influence tax avoidance. Independent commissioners are not able to moderate the relationship between executive compensation, executive risk preferences, and political connections with tax avoidance. This indicates that the role of independent commissioners does not weaken the relationship between these variables and tax avoidance. The audit committee is also unable to moderate the relationship between executive compensation and political connections with tax avoidance. This indicates that the audit committee does not weaken this relationship. Nevertheless, the audit committee is capable of moderating the relationship between executive risk preferences and tax avoidance. This result indicates that the audit committee strengthens the relationship between executive risk preferences and tax avoidance.